A NEW METHOD TO ESTIMATE FINITE LIFE OF NOTCHED COMPONENTS UNDER VARIABLE AMPLITUDE FATIGUE LOADING - ZHANG Wei; HU MingMin (Jixie qiangdu)
Based on uniaxial fatigue research,starting from the fatigue mechanism,a strain energy density and strength interference model based on the strain cyclic loading has been studied. The energy dissipation is equivalent to the stress growth.The relation of internal stress applied stress and the intrinsic strength has been established,Then consider the effect of notch stress gradient,make a research on the notched specimens of multiaxial loading fatigue life formula and the stress concentration factor with three different samples of experimental data to verify the correctness of the model under study. Preliminary research indicates that the model have a satisfied prediction ability for the referenced multiaxial fatigue test data.